Porno?Chic! : how pornography changed the world and made it a better place. - McNair, Brian (Taylor and Francis, 2013)
Porno? Chic! examines the relationship between the proliferation of pornography and sexualised culture in the West and social and cultural trends which have advanced the rights of women and homosexuals.